2018
DOI: 10.1259/dmfr.20170399
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the accuracy of periapical radiography with CBCT taken at 3 different voxel sizes in detecting simulated endodontic complications: an ex vivo study

Abstract: CBCT images may be useful as an adjunct to periapical imaging in the detection of endodontic complications, such as strip perforation and overfilled root canals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 37 publications
1
15
0
2
Order By: Relevance
“…A previous investigation focused on detecting the same simulated endodontic complications as this study, and compared the accuracy of intraoral periapical radiography with CBCT taken at three different voxel sizes (Koç et al . ). The findings suggested that CBCT images obtained between 0.1 mm and 0.2 mm voxel size would be useful for detecting endodontic complications.…”
Section: Discussionmentioning
confidence: 97%
“…A previous investigation focused on detecting the same simulated endodontic complications as this study, and compared the accuracy of intraoral periapical radiography with CBCT taken at three different voxel sizes (Koç et al . ). The findings suggested that CBCT images obtained between 0.1 mm and 0.2 mm voxel size would be useful for detecting endodontic complications.…”
Section: Discussionmentioning
confidence: 97%
“…Another factor that can influence image quality is the voxel size, which can range from 0.085 to 0.4 mm, depending on the technical specifications of each CBCT apparatus (Rosen et al , Koç et al ). Although smaller voxel sizes act to improve the spatial resolution thus providing more detail in the image (Cebe et al ), a higher dose of radiation is necessary to generate high‐quality images (Venskutonis et al ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the guidelines of AAE & AAOMR Joint Position Statement () and ESE (), CBCT examinations are indicated only in cases where two‐dimensional techniques do not provide sufficient information for a diagnosis and treatment plan, due to the high radiation dosage and cost when compared to intraoral radiographs (Koç et al ). In the present study, intraoral radiographs were not included, since their use in the detection of fractured instruments is well documented (Rosen et al , Ramos Brito et al ) and have also been compared with CBCT images (Rosen et al , Ramos Brito et al ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations